Entertainment-Education Behind the Scenes Case Studies for Theory and Practice - Frank, Lauren B.; Falzone, Paul (Springer Nature, 2021)
This Open Access book tracks the latest trends in the theory, research, and practice of entertainment-education, the field of communication that incorporates social change messaging into entertaining media. Sometimes called edutainment, social impact television, narrative persuasion, or cultural strategy, this approach to social and behavior change communication offers new opportunities including transmedia and digital formats. However, making media can be a chaotic process. The realities of working in the field and the rigid structures of scholarly evaluation often act as barriers to honest accounts of entertainment-education practice. In this collection of essays, experienced practitioners offer unique insight into how entertainment-education works and present a balanced view of its potential pitfalls. This book gives readers an opportunity to learn from the successes and mistakes of the experts, taking a behind-the-scenes look at the business of making entertainment-education media.